CARBON, OXYGEN AND STRONTIUM ISOTOPE RECORDS OF DEVONIAN BRACHIOPOD SHELL CALCITE - van Geldern R.; Joachimski M.M.; Day J.; Jansen U.; Alvarez F.; Yolkin E.A.; Ma X.-P. (My University, 2006)
Devonian brachiopod shells from North America, Spain, Morocco, Siberia, China and Germany were analysed for δ13C, δ18O and 87Sr/86Sr. The samples were screened for diagenetic alteration by means of cathodoluminescence, trace element chemistry (Sr, Mn, Fe) and scanning electron microscopy. 409 out of 1678 shells ranging from the middle Emsian to the middle Famennian were accepted as well-preserved. 87Sr/86Sr ratios start with values of 0.70860 in the Lochkovian and decline continuously to 0.70782 at the Emsian-Eifelian boundary. This decrease is attributed to a reduced riverine strontium flux caused by the termination of the Caledonian orogeny. For the Eifelian and Givetian, relatively uniform values between 0.70782 and 0.70784 are observed. 87Sr/86Sr ratios start to rise again in the late Givetian and reach a value of 0.70807 in the early Famennian. An enhanced continental delivery of strontium as consequence of tectonic uplift due to the Eovariscan orogeny, in combination with climatic warming, as suggested by the δ18O record, is interpreted to be responsible for the shift to more radiogenic strontium isotope values. The carbon isotope curve shows four positive δ13C excursions with amplitudes ranging from + 2.0‰ and + 3.5‰. The positive excursion observed in the australis Zone coincides with the deposition of the Bakoven black shale in New York state. The δ13C excursion near the Eifelian-Givetian boundary is correlated with the Kacàk event while the two positive excursions in the late Frasnian and at the Frasnian-Fammenian transition are contemporaneous with the deposition of the Kellwasser horizons. All carbon isotope excursions are interpreted to be the result of increased burial of organic carbon. The oxygen isotope record reveals short-term excursions in the late Givetian, late Frasnian and at the Frasnian-Famennian transition which are interpreted to result from changes in surface water temperature. The long-term evolution in δ18O shows values of - 2.8‰ to - 3.5‰ in the Early and Middle Devonian to generally lower δ18O values between - 4.3‰ and - 6.1‰ in the latest Givetian and Late Devonian. Assuming a δ18O of Devonian seawater of - 1‰ V-SMOW, Early and Middle Devonian δ18O values translate into realistic palaeotemperatures (24 to 27 °C) for tropical to subtropical latitudes. In contrast, the δ18O values of Late Devonian brachiopods indicate a shift to unrealistically warm palaeotemperatures (31 to 41 °C). The change in δ18O of brachiopod calcite cannot be explained solely by a change in temperature, pH or by a secular decrease in δ18O of seawater. A combination of climatic warming and a moderate decrease in δ18O of seawater from the Middle to Late Devonian may account for the observed decrease in δ18O of brachiopod calcite. However, this tentative interpretation is not confirmed by conodont apatite δ18O data that translate into warm but realistic Late Devonian palaeotemperatures. © 2006 Elsevier B.V. All rights reserved.
Keywords: BRACHIOPODS; CARBON ISOTOPES; DEVONIAN; OXYGEN ISOTOPES; STRONTIUM ISOTOPES; Paleozoic::Devonian; Палеозой::Девонская